FAKTOR KETIMPANGAN AKSES SARANA BELAJAR ANAK DALAM MENGHADAPI PENDIDIKAN BERKUALITAS YANG BELUM MERATA - Silvia Ayu Tri Octavia; Azharina Eka Rahmawati; Indah Prabawati (Yayasan Nusantara Hasana Berdikari, 2026)
Inequality in children's access to learning facilities remains a major issue in achieving quality education in Indonesia, particularly in remote and underdeveloped regions. This study aims to analyze the factors contributing to this inequality and to understand the actual conditions in the field. The research employs a literature review approach by examining various scientific sources, including academic journals, books, and reports from international organizations. The findings indicate that inequality is influenced by economic factors, limited educational infrastructure, uneven distribution of teachers, and disparities in access to technology. In addition, the suboptimal implementation of education policies further exacerbates the problem. These findings highlight the need for comprehensive policies, improved supervision, and multi-stakeholder collaboration to create a more inclusive and equitable education system.